The Judicial Model of Prophet Muhammad (PBUH): A Conceptual Reconstruction Toward a Humanistic Modern Legal System - Pratiwi, Arini; Rachmadani; Muthalib, Lian Mulyani; Hanafi, Syawaluddin (Al-'Adl, 2025)
The need for a judicial system that is not only legal-formal but also substantive and just has become increasingly urgent amidst the ongoing crisis of integrity and public trust in modern judicial institutions. This research stems from the urgency to re-explore the realities of the pre-Islamic Arab judicial system and the system during the time of Prophet Muhammad (PBUH), which emphasized transcendental justice, ethics, and the values of public interest (maṣlaḥah). The study aims to examine the characteristics of the judicial systems in pre-Islamic Arabia and during the Prophet's era, as well as how the principles and methods applied in that context can be compared to and contribute to the development of modern judicial systems. The method used in this study is normative legal research based on library research, employing historical, conceptual, and comparative approaches. Data were collected from primary sources such as the Qur’an and Hadith, as well as secondary sources including classical and contemporary works on Islamic law and judicial systems. The study finds that the judicial system during the Prophet’s time was not formally institutionalized, yet it already embodied fundamental principles of modern justice—such as impartiality, presumption of innocence, equality before the law, and a substantive form of appellate review. Prophet Muhammad (PBUH) applied six main methods for resolving disputes: iqrār (confession), bayyinah (evidence/witness), yamin (oath), qasāmah (collective oath), firasah (judicial intuition and reasoning), and ṣulḥ (mediation). These methods demonstrate that the Prophetic system was flexible, contextual, and highly responsive to the social dynamics of the time. In conclusion, the Islamic judicial system during the Prophet’s era is not merely a historical legacy but a paradigmatic model that remains relevant for strengthening contemporary legal systems. Integrating the ethical and transcendental values of the Prophetic model into modern judiciary is believed to enhance the trajectory of law toward dignified and humanistic justice.